Implementation of the Just-in-Time System to Improve Inventory Efficiency at PT Unilever Indonesia Tbk - Siti Sa’adah; Neyla Mutiara Sabrina; Elsa Rosmiati Alisa; Vini Limbong; Asri Sundari (Advances in Management & Financial Reporting, 2026)
Purpose: This study aims to describe the characteristics of inventory management and operating cash flow at PT Unilever Indonesia Tbk based on an analysis of its financial statements. Research Method: This study employs a descriptive quantitative approach using a documentary study method. Secondary data were obtained from the Interim Financial Reports of PT Unilever Indonesia Tbk for the periods ending March 31, 2024, and March 31, 2025, as well as the 2024 Annual Report. The analysis was conducted using the Inventory Turnover Ratio (ITO), Days Sales of Inventory (DSI), trend analysis, and a review of inventory accounting policies. Results and Discussion: The results show that inventory value increased by 12%, the Inventory Turnover Ratio decreased from 3.20 to 2.67 times, and Days Sales of Inventory increased from 28.1 to 33.7 days. In addition, cash and cash equivalents increased by 61%, while net cash flow from operating activities turned from negative to positive in the first quarter of 2025. These findings illustrate changes in inventory management and operating cash flow based on financial statement data. Implications: Financial ratio analysis can serve as a starting point for evaluating inventory management practices, but it requires operational data to support a more comprehensive interpretation. Originality: This study integrates an analysis of inventory ratios, operating cash flow, and inventory accounting policies at FMCG companies in Indonesia using data from publicly available financial statements.